Retraction Notice - Fatty liver disease might increase the risk of abdominal operation in patients with fatty liver and the prevalence of cancer in first-degree relatives - AVES Editorial Office, (Turkish Journal of Gastroenterology, 2019)
Retraction NoticeThe following article is retracted from publication in Turkish Journal of Gastroenterology by decision of editors of the journal since it is a duplicate publication, which has been previously published in Wien Klin Wochenschr. 2015 Apr 14 DOI: 10.1007/s00508-015-0744-4 Duplicate publicationFatty liver disease might increase the risk of abdominal operation in patients with fatty liver and the prevalence of cancer in firstdegree relatives Metin Başaranoğlu1, Billur Canbakan2, Kemal Yıldız3, Bahadır Ceylan4, Birol Baysal3, Ömer Uysal5, Hakan Şentürk3 1Department of Gastroenterology, Türkiye Yüksek İhtisas Hospital, Ankara, Turkey2Department of Gastroenterology, İstanbul University Cerrahpaşa Faculty of Medicine, İstanbul, Turkey3Department of Gastroenterology, Bezmialem Vakif University Faculty of Medicine, İstanbul, Turkey4Department of Clinical Microbiology and Infectious Diseases, Medipol University Hospital, İstanbul, Turkey5Department of Biostatistics, Bezmialem Vakif University Faculty of Medicine, İstanbul, TurkeyTurk J Gastroenterol 2014; 25 (Suppl.-1): 138-41DOI: 10.5152/tjg.2014.7674  Original publicationNonalcoholic fatty liver may increase the risk of operation in patients with fatty liver and the frequency of cancer in their firstdegree relatives. Metin Başaranoğlu1, Billur Canbakan2, Kemal Yıldız3, Bahadır Ceylan4, Birol Baysal3, Ömer Uysal5, Hakan Şentürk3 1Department of Gastroenterology, Türkiye Yüksek İhtisas Hospital, Ankara, Turkey2Department of Gastroenterology, İstanbul University Cerrahpaşa Faculty of Medicine, İstanbul, Turkey3Department of Gastroenterology, Bezmialem Vakif University Faculty of Medicine, İstanbul, Turkey4Department of Clinical Microbiology and Infectious Diseases, Medipol University Hospital, İstanbul, Turkey5Department of Biostatistics, Bezmialem Vakif University Faculty of Medicine, İstanbul, TurkeyWien Klin Wochenschr. 2015 Apr 14DOI: 10.1007/s00508-015-0744-4